An exploration of females who use socially intrusive behaviours: from psychological characteristics to treatment - Wylie, Nicola (2013)
This thesis explores the relatively unknown area of female stalkers. Throughout the thesis the newly defined term ‘Socially Intrusive Behaviours’ (SIBs) is used to unify previous stalking definitions. Chapter One provides an introduction to the topic of females who display SIBs. Chapter Two includes a Thematic Analysis and explores the motives and justifications for SIBs and examines the personality traits, attachment styles and experiences of anger with female patients. Results indicate that SIBs are a maladaptive coping strategy that benefit the perpetrator, provide feelings of safety, are a response to perceived threats of abandonment and require over-control of emotional arousal. Assessment of personality, anger and attachment are also examined and treatment recommendations are discussed. An interesting finding was that SIBs are a maladaptive coping strategy to manipulate the perpetrators’ feelings rather than the feelings or actions of others. Dialectical Behavioural Therapy (DBT) is a recognised treatment which targets a range of maladaptive coping strategies. Chapter Three provides a systematic review of the effectiveness of DBT with female-only populations in Randomised Control Trials. Results found DBT was superior at reducing a range of maladaptive coping behaviours including self-harm, substance misuse and binge/purge eating. It was therefore considered a potentially useful intervention for females whose maladaptive coping strategies are SIBs. Whether DBT could effectively target an adult female patient’s SIBs was tested by a single case study in Chapter Four. The results indicated that DBT reduced her SIBs and improved her anger management skills. Chapter Five is a critique of the State Trait Anger Expression Inventory (Spielberger, 1999) as used in Chapter Two and Four. Chapter Six discusses the clinical and theoretical implications of this thesis, explores its limitations, and provides recommendations for future research.